2022
DOI: 10.3389/fpsyg.2022.801614
|View full text |Cite
|
Sign up to set email alerts
|

Parenting and Children’s Behavior During the COVID 19 Pandemic: Mother’s Perspective

Abstract: Since the onset of the COVID-19 pandemic, many parents have felt anxious, overwhelmed, and stressed out due to the changes in education and family and working routines. This work aimed to (a) describe three dimensions of perceived parenting (positive parenting, parenting stress, and parental school support) in the COVID-19 pandemic context, (b) describe possible changes perceived by mothers in their children’s behavior during the social isolation phase, (c) analyze if behavioral changes vary according to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
1
0
1
Order By: Relevance
“…This condition led to changes in the patient's interest in receiving maternal health services from the CHCs. The changes in service delivery were associated with the client's visit ( Hazfiarini et al, 2022 ; Vargas et all 2022 ; Atmuri et al, 2022 ). Similarly, Haiti experienced the antenatal care and delivery visit reduction at the maternal healthcare facilities due to the strict regulations of the COVID-19 ( Aranda et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This condition led to changes in the patient's interest in receiving maternal health services from the CHCs. The changes in service delivery were associated with the client's visit ( Hazfiarini et al, 2022 ; Vargas et all 2022 ; Atmuri et al, 2022 ). Similarly, Haiti experienced the antenatal care and delivery visit reduction at the maternal healthcare facilities due to the strict regulations of the COVID-19 ( Aranda et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…They examined the correlation between parental stress levels and the cognitive functioning of second-grade students in the Philippines. Rubilar et al (2022) mentioned that parenting dimensions, as perceived by individuals, influenced children's behavior. Mothers who exhibited higher levels of positive parenting tended to report more significant changes in their children's behavior.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies still believe that parents do not influence children in family education, but children's behavior influences parents (Maccoby, 2000). A study during the pandemic showed that some parents, especially mothers, felt stressed and out of control because of their children's behavior, which negatively affected children's moral cognitive development (Vargas Rubilar et al, 2022). Because babies need to be cared for uninterruptedly, parents will sacrifice some sleep time to care for their children.…”
Section: How Children Influence Parentsmentioning
confidence: 99%